Faktor Budaya Dalam Pembangunan Bakat Manusia Menurut Perspektif Islam: Satu Tinjauan: (Cultural Factors in the Development of Human Talent According to the Islamic Perspective: A Review) - Ibrahim, Tajul Nizam; Hussin, Zaharah; Abdul Razak, Ahmad Zabidi (Online Journal of Research in Islamic Studies, 2024)
Islam emphasizes the development of human talents in line with individual potential and abilities. Each person possesses different spiritual and physical capacities (spiritual, emotional, physical and intellectual) within different environments. As we explore, these potentials and abilities are unique with specific characteristics. They cannot, however be optimally developed due to various constraints. This article aims to present factors influencing human talent development from an Islamic perspective. The study data obtained through document analysis method. The findings indicated that factors contributing to human talent development from an Islamic perspective are significantly influenced by both individual traits and the surrounding environment. These findings can serve as a guide in managing one’s talent to fulfill the gifts and potential granted by Allah to humanity.